Analisis Pengaruh Beban Kerja Terhadap Kinerja Karyawan Pada PT XYZ Cabang Cibitung Dengan Menggunakan Uji Regresi Linier Sederhana - Risa Sabila; Fahriza Nurul Azizah (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this research is to determine the effect of workload on employee performance at PT XYZ Cibitung Branch. Data is processed using research samples at the company. Analysis of processed data results was carried out using a simple linear regression test and the Determination Coefficient Test (R2). The results obtained include; Simple linear regression test states that workload does not significantly affect employee performance; And the Determination Coefficient Test (R2) said that 21.9% of the workload affected employee performance and the rest of 78.1% was influenced by other factors that were not discussed into the study.